Characteristic Features of Rainfall and Meteorological Droughts in Jhunjhunu District of Arid Rajasthan - Rao, A S; Poonia, Surendra (Annals of Arid Zone, 2016)
The rainfall characteristics and meteorological drought conditions in Jhunjhunu district of arid Rajasthan were studied using six tehsil-wise rainfall data (1901-2011). The district experiences 405 to 560 mm of annual rainfall in 26 to 34 rainy days with a coefficient of variation of 37 to 44%. The seasonal rainfall (June-September) varied from 343 to 477 mm in 18 to 24 rainy days. The highest annual rainfall recorded in the district was between 828 mm at Jhunjhunu and 1252 mm at Khetri. Similarly, the lowest rainfall record varied between 89 mm at Khetri and 187 mm at Udaipurwati. The extreme rainfall events recorded in the Jhunjhunu district showed that 1-day highest rainfall varied from 158 mm at Jhunjhunu to 281 mm at Khetri. The 1-day rainfall was lowest at Jhunjhunu (82.8 mm, 98.1 mm, 117.2 mm, 131.5 mm and 146.0 mm) and highest at Buhana (116.5 mm, 143.0 mm, 176.0 mm, 200.7 mm and 225.8 mm) for all return periods (5, 10, 25, 50 and 100 years). The long-term annual rainfall trends showed that there was a marginal increase at a rate 0.43 mm year-1 at Jhunjhunu, 0.48 mm year-1 at Khetri, 0.74 mm year-1 at Chirawa. The meteorological droughts prevailed in 36 years out of 111 years (1901-2011) with lowest frequency of 32 years with drought at Jhunjhunu and Chirawa to a highest frequency of 35 years drought at Khetri. The decade 1981-90 experienced highest (6 out of 10 years) number of moderate to severe droughts, whereas the 1941-50 recorded least frequency (2 out of 10 years) of droughts. Key words: Rainfall characteristics, meteorological drought, Jhunjhunu district.